دور الإعلام التربوي في وزارة التربية العراقية في الحد من مستويات الأمية: دراسة تطبيقية على عينة من الاختصاصيين التربويين - الجبوري، هديل علي محي عباس; عسكري، حسين شريف (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
هدفت البحث إلى الكشف عن دور الإعلام التربوي في وزارة التربية العراقية في الحد من مستويات الأمية وهي دراسة تطبيقية على عينة من الاختصاصيين التربويين، وقد استخدم لهذا الأمر من المقابلات التي أجريت مع ١٥ شخصا من خبراء الإعلام وخبراء التربية، والأداة الأصلية في هذا البحث هي نظام تصنيف المفاهيم المستخرجة، وتم في هذه البحث ترميز نصوص وجهات نظر المفحوصين حول أسئلة المقابلات في 272 رمزا واستخرج ٤٦ رمزا أوليا منها، وتوصلت البحث إلى نتائج عديدة أهمها كان تأكيد خبراء التربية على (تنوع البرامج ومرونتها لإرضاء جميع الأذواق ومختلف الفئات)، (تزويد المتعلمين مجانا أو بأقل كلفة في أسرع وقت)، (بث البرامج التعليمية على القنوات الفضائية التابعة للوزارة) (التنسيق الإعلامي مع الخطوط العريضة)، (استخدام البحث الإلكترونية بالإضافة إلى البحث الحضورية)، (التأكيد على رسم الأهداف التطبيقية والتخطيط لتحقيق الأهداف)، (نشر حملات التوعية التي تدعو إلى محاربة الأمية) و(اتخاذ المناهج المعتمدة الوطنية والدولية)، فيما أكد خبراء الإعلام أكثر على (التخطيط على أساس احتياجات ورغبات المتعلمين)، (التخطيط للحد من ظاهرة التسرب الدراسي)، (استخدام أساليب التعلم الحديثة بشكل فعال ومبتكر)، (استخدام الآليات القانونية للقضاء على الأمية)، و(ضرورة استخدام آراء خبراء الإعلام)، كما بين خبراء التربية أن أهم أدوار الإعلام التربوي في الاستفادة من التكنولوجيا الحديثة لوزارة التربية العراقية في الحد من الأمية هي (مواكبة التطورات الحديثة في استخدام وسائل التعليم الحديثة)، (استخدام مواقع التواصل الاجتماعي) و(استخدام الوسائل التعليمية التوضيحية)، بالمقابل اعتبر خبراء الإعلام أن أهم أدوار الإعلام التربوي في الاستفادة من التكنولوجيا الحديثة لوزارة التربية العراقية في الحد من الأمية هي (استخدام أدوات الاتصال الجماهيري في دعاية محو الأمية). The research aimed to reveal the role of educational media in the Iraqi Ministry of Education in reducing illiteracy levels. It is an applied study on a sample of educational specialists. For this purpose, interviews were conducted with 15 people from media experts and education experts, and the original tool in this research is the system. Classification of the extracted concepts. In this research, the texts of the subjects’ viewpoints on the interview questions were coded into 272 codes and 46 initial codes were extracted from them. The research reached many results, the most important of which was the education experts’ emphasis on (the diversity of programs and their flexibility to satisfy all tastes and different groups), (providing Learners for free or at the lowest cost as quickly as possible), (broadcasting educational programs on satellite channels affiliated with the Ministry), (media coordination with bold lines), (using electronic research in addition to in-person research), (emphasis on setting applied goals and planning to achieve goals), (Publishing awareness campaigns that call for combating illiteracy) and (adopting approved national and international curricula), while media experts emphasized more on (planning based on the needs and desires of learners), (planning to reduce the phenomenon of school dropout), (effective use of modern learning methods). And innovative), (using legal mechanisms to eliminate illiteracy), and (the necessity of using the opinions of media experts). Educational experts also stated that the most important roles of educational media in benefiting from the modern technology of the Iraqi Ministry of Education in reducing illiteracy is (keeping pace with modern developments in the use of media. Modern education), (using social networking sites) and (using explanatory educational means), on the other hand, media experts considered that the most important roles of educational media in benefiting from the modern technology of the Iraqi Ministry of Education in reducing illiteracy is (using mass communication tools in literacy propaganda).
Keywords: علم النفس التربوي -- التقنيات التعليمية -- الوسائل الإعلامية -- محو الأمية -- العراق